Examining racial and ethnic disparities in adult emergency department patient visits for concussion in the United States - Lempke, Landon B.; Kerr, Zachary Yukio; Melvin, Patrice; Walton, Samuel R.; Wallace, Jessica S.; Mannix, Rebekah C.; Meehan, William P.; Ward, Valerie L. (Frontiers in Neurology, 2022)
Background: Racial and ethnic differences in Emergency Department (ED) visits have been reported among adolescent patients, but are unsubstantiated among adults. Our purpose was to examine the relationship between race/ethnicity and adult concussion ED visits, their injury mechanisms, and Computed Tomography (CT) scan use among a nationally representative sample. Methods: We used the National Hospital Ambulatory Medical Care Survey database from 2010-2015 to examine 63,725 adult (20-45 years old) patient visits representing an estimated 310.6 million visits presenting to EDs. Of these visits, 884 (4.5 million national estimate) were diagnosed with a concussion. Visit records detailed patient information (age, sex, race/ethnicity, geographic region, primary payment type), ED visit diagnoses, injury mechanism (sport, motor vehicle, fall, struck by or against, “other”), and head CT scan use. Race/ethnicity (non-Hispanic Asian, non-Hispanic Black or African American, Hispanic/Latinx, non-Hispanic multiracial or another, and non-Hispanic White) was the primary independent variable. We used multivariable logistic and multinomial regression models with complex survey sampling design weighting to examine the relationship between concussion ED visit, injury mechanism, and CT scan use separately by race/ethnicity, while accounting for covariates. Results: There were no associations between race/ethnicity and concussion diagnosis among adult ED visits after accounting for covariates. Relative to sports-related injuries, non-Hispanic Black or African American patient visits were associated with motor vehicle (OR=2.69, 95%CI:1.06-6.86) and “other” injury mechanism (OR=4.58, 95%CI:1.34-15.69) compared to non-Hispanic White patients. Relative to sports-related injuries, non-Hispanic Asian, Multiracial, or patients of another race had decreased odds for falls (OR=0.20, 95%CI:0.04-0.91) and “other” injuries (OR=0.09, 95%CI:0.01-0.55) compared to non-Hispanic White patients. The odds of a CT scan being performed were significantly lower among Hispanic/Latinx patient visits relative to non-Hispanic White patients (OR=0.52, 95%CI:0.30,0.91), while no other race/ethnicity comparisons differed. Conclusion: Our findings indicate that the overarching concussion ED visit likelihoods may not differ by race/ethnicity in adults, but the underlying mechanism causing the concussion and receiving a CT scan demonstrate considerable differences. Prospective research is warranted to comprehensively understand and intervene on the complex, multi-level race/ethnicity relationships related to concussion health care to ensure equitable patient treatment.